The Affordable Care Act Attenuates Financial Strain According to Poverty Level. (24th July 2018) - McKenna, Ryan M.; Langellier, Brent A.; Alcalá, Héctor E.; Roby, Dylan H.; Grande, David T.; Ortega, Alexander N.
We use data from the 2011-2016 National Health Interview Survey to examine how the Patient Protection and Affordable Care Act (ACA) has influenced disparities in health care–related financial strain, access to care, and utilization of services by categories of the Federal Poverty Level (FPL). We use multivariable regression analyses to determine the ACA's effects on these outcome measures, as well as to determine how changes in these measures varied across different FPL levels. We find that the national implementation of the ACA's insurance expansion provisions in 2014 was associated with improvements in health care–related financial strain, access, and utilization. Relative to adults earning more than 400% of the FPL, the largest effects were observed among those earning between 0% to 124% and 125% to 199% of the FPL after the implementation of the ACA. Both groups experienced reductions in disparities in financial strain and uninsurance relative to the highest FPL group. Overall, the ACA has attenuated health care–related financial strain and improved access to and the utilization of health services for low- and middle-income adults who have traditionally not met income eligibility requirements for public insurance programs. Policy changes that would replace the ACA with less generous age-based tax subsidies and reductions in Medicaid funding could reverse these gains.